CB2 Cannabinoid Receptors as a Therapeutic Target—What Does the Future Hold? - Dhopeshwarkar, Amey; Mackie, Ken (Molecular pharmacology, 2014)
The past decades have seen an exponential rise in our understanding of the endocannabinoid system, comprising CB1 and CB2 cannabinoid receptors, endogenous cannabinoids (endocannabinoids), and the enzymes that synthesize and degrade endocannabinoids. The primary focus of this review is the CB2 receptor. CB2 receptors have been the subject of considerable attention, primarily due to their promising therapeutic potential for treating various pathologies while avoiding the adverse psychotropic effects that can accompany CB1 receptor–based therapies. With the appreciation that CB2-selective ligands show marked functional selectivity, there is a renewed opportunity to explore this promising area of research from both a mechanistic as well as a therapeutic perspective. In this review, we summarize our present knowledge of CB2 receptor signaling, localization, and regulation. We discuss the availability of genetic tools (and their limitations) to study CB2 receptors and also provide an update on preclinical data on CB2 agonists in pain models. Finally, we suggest possible reasons for the failure of CB2 ligands in clinical pain trials and offer possible ways to move the field forward in a way that can help reconcile the inconsistencies between preclinical and clinical data.